2003
DOI: 10.1590/s0102-311x2003000500025
|View full text |Cite
|
Sign up to set email alerts
|

Consumo alimentar da população adulta segundo perfil sócio-econômico e demográfico: Projeto Bambuí

Abstract: A nutritional survey was performed in a random sample of 546 individuals (ages 18and over) in a city named Bambuí (15,000 inhabitants)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
20

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 19 publications
(30 reference statements)
2
12
0
20
Order By: Relevance
“…Evidence corroborates earlier findings that associate female gender with treatment and control of high blood pressure 4,23,24 , an association observed after adjusting for potential confounders, such as the use of health services. Although the male gender is underrepresented in this study -due to daytime employment obligations -participating elderly men showed a tendency to negate illness, downplay symptoms, resist help, forgo appointments, terminate care and carry out self-treatment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Evidence corroborates earlier findings that associate female gender with treatment and control of high blood pressure 4,23,24 , an association observed after adjusting for potential confounders, such as the use of health services. Although the male gender is underrepresented in this study -due to daytime employment obligations -participating elderly men showed a tendency to negate illness, downplay symptoms, resist help, forgo appointments, terminate care and carry out self-treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Without a compass to navigate uncharted conceptual waters, we forged our own methodological pathway. First, we critically reviewed background anthropological evidence on this setting 12,23 . Initial descriptive findings stimulated a search for new epidemiological correlates of adequate pressure control.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite was observed in terms of the health indicator physical activity. Compared to men, Brazilian women have healthier diets and lower levels of leisure-time physical activity 27,28 , indicating coherence between these data. Nonetheless, somewhat surprising findings were also found.…”
Section: Discussionmentioning
confidence: 87%
“…Também se destacam as próprias restrições impostas pelo tratamento como desencadeantes de percepções desagradáveis (6) que podem gerar estresse. Por sua vez, a qualidade de vida que se perde com o estresse influencia negativamente no desejo em manter o tratamento (4) por interferir no desejo de viver bem e melhor.…”
Section: Introductionunclassified
“…(1) . Estima-se que a enfermidade atinja cerca de 30% da população adulta, especialmente os idosos, e afirma-se seu envolvimento com os óbitos por doença isquêmica do coração e acidente vascular encefálico(1) .Já foram relatados o papel da obesidade, a influência do sexo, a ingestão de sódio, o baixo consumo de potás-sio, o consumo exacerbado de álcool, a raça negra, o sedentarismo, a história familiar, a baixa escolaridade e o uso de medicamentos, como os contraceptivos orais, na gênese da HAS (1)(2) .Por conseguinte, questões relativas à manutenção da saúde mental em virtude dos determinantes psicossociais desta doença descritos na literatura, em especial o estresse (1,3) que foi identificado como causa da elevação dos valores pressóricos e responsável pela gênese da HAS (4) , uma vez que provoca o aumento da reatividade cardiovascular (1,5) .Também se destacam as próprias restrições impostas pelo tratamento como desencadeantes de percepções desagradáveis (6) que podem gerar estresse. Por sua vez, a qualidade de vida que se perde com o estresse influencia negativamente no desejo em manter o tratamento (4) por interferir no desejo de viver bem e melhor.…”
unclassified